EFEKTIVITAS PENYELENGGARAAN ADMINISTRASI DESA DALAM MENUNJANG PEMBANGUNAN (Desa Lemahino Kecamatan Tobelo Selatan Kabupaten Halmahera Utara) - BOBOROS, YUNITA; PANGKEY, MASJE; RURU, JOORIE MARHAEN (Sam Ratulangi University, 2015)
ABSTRACTEffective administration of the village is needed to support rural development, namely as a source ofdocuments and information in rural development planning. Therefore, the government continues tomake improvements on the village administration, among others, by issuing Regulation Number 32 of2006 on Village Administration. This study aimed to know how to transform the effectiveness of theadministration of the village in the village Lemahino, and the extent of the effectiveness of theimplementation of the village administrasu supporting development in rural Lemahino.This study used qualitative methods. The informants as many as 10 people were taken by usingpurposive of the various elements of the village government, BPD, LPM, PKK, social organization /social, leaders / village community leaders and villagers. The data was collected using interviewtechniques and equipped with a documentary and observation techniques. The documents analysistechnique used is the qualitative analysis of interactive model of Miles and Hubernann.Based on these results it can draw the following conclusions: (1) administrative Penyelenggaaraanvillage (village administration books), good public administration, administrative resident, financialadministration, and the administration of rural development Lemahino not yet fully effective, but it isgood enough. (2) The effectiveness of the administration of the village in supporting development inrural Lemahino pretty good but not maximized.Conclusions based on these results it is necessary to put forward the following suggestions: (1) Theeffectiveness of the administration of the village in the village Lemahino should be improved. It urgesthat must be done is to increase the village administration of human resources, provision of adequateresources allocation, and the provision of facilities and infrastructure of the village administration andadequate representative. (2) The planning of rural development should always be based on documentsand information that is accurate and reliable. To the village government and community agenciesconcerned in the preparation of village development plan should refer to the documents that have beenprocessed in the books related administrative villages.Keywords: village administration, village development.